2013
DOI: 10.1080/08946566.2013.780944
|View full text |Cite
|
Sign up to set email alerts
|

A Description of Cases of Severe Physical Abuse in the Elderly and 1-Year Mortality

Abstract: We conducted a case-control study to evaluate severe physical abuse of the elderly treated in two Chicago area Level I trauma centers. This report details whether physicians are adequately reporting cases of abuse to Adult Protective Services (APS), and assesses 1 year. The failure to report two-thirds of the cases and the substantially higher risk of death during the first year after hospitalization indicates the need for improved identification, reporting, and intervention. It is important that clinicians un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…33-35 Reliance on the larger literature of intimate partner violence is relevant to improve understanding of injuries in physical elder abuse because some elder abuse is “domestic violence grown old,” family violence that began earlier in life and persists into old age. 16,36 …”
Section: Discussionmentioning
confidence: 99%
“…33-35 Reliance on the larger literature of intimate partner violence is relevant to improve understanding of injuries in physical elder abuse because some elder abuse is “domestic violence grown old,” family violence that began earlier in life and persists into old age. 16,36 …”
Section: Discussionmentioning
confidence: 99%
“…20 This is likely due to a poor understanding of elder abuse among trauma service clinical staff and inadequate training regarding the proper procedures for reporting suspected incidents. 20 Very little research has examined severe traumatic injuries in victims of physical elder abuse.…”
Section: Discussionmentioning
confidence: 99%
“…20 This is likely due to a poor understanding of elder abuse among trauma service clinical staff and inadequate training regarding the proper procedures for reporting suspected incidents. 20 Very little research has examined severe traumatic injuries in victims of physical elder abuse. Friedman and colleagues, in a case-control study comparing victims of severe physical elder abuse to other trauma victims, found that elder abuse victims had more severe injuries, were more commonly female, were more likely to abuse drugs or alcohol, and more frequently had dementia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations